The influence of risk classification and community affiliation on the acceptance of user-innovated medical devices - Jakob Fiedler; André Schorn; Cornelius Herstatt (Hamburg University of Technology (TUHH), Institute for Technology and Innovation Management (TIM), 2023)
User innovation contributes significantly to societal advancement, particularly in developing novel products and services, offering substantial financial potential, and fostering the common good. This is particularly evident in medical science, where it addresses diverse needs and is often shared at minimal or no cost. However, the diffusion of user-innovated products remains limited and research on the perception of user-innovated products is rather scarce, reducing their potential contributions to the common good. This paper investigates end-users' perceptions of user innovation, a critical yet underexplored aspect of diffusion. Specifically, using a mixed-methods approach, we examine the influence of product risk classification and community development on the perception of user-innovated medical devices. This study combines qualitative research through semi-structured interviews (n=5) and quantitative research using a 2x3 (User Innovation vs. Producer Innovation; Product risk classification I, II, III) between-subject experiment (n=301). Our findings reveal that end-users evaluate user-innovated and traditionally-innovated products differently based on various criteria. User-innovated products are perceived as more pleasant and attractive, while traditionallyinnovated products are viewed as safer and of higher value. This effect is more pronounced for products with higher risk classifications. However, the perceived lower safety and value of user innovation products result in a reduced willingness to purchase among end-users. Additionally, we find that community-developed user-innovated products consistently outperform in all evaluation categories compared to "pure" user-innovated products.
Keywords: 330; User Innovation; Medical Engineering; Diffusion of Innovation; MMR; Consumer Acceptance